Assessment of potential cellular toxicity of methylglyoxal on primary human epidermal keratinocytes - Prakoso, Nurul Muhammad; Sundari, Ayu Mulia; Fadhilah; Abinawanto; Dwiranti, Astari; Bowolaksono, Anom (Current Research on Biosciences and Biotechnology, 2025)
Skin is the outermost layer of the human body, which is important to prevent damage by infection, ultraviolet radiation, and toxic materials. The impermeable barrier of the skin has to be maintained via skin regeneration to preserve its essential function. However, skin regeneration declines due to decreased cell proliferation during skin aging. In this study, we investigated the role of methylglyoxal (MGO) as a precursor of advanced glycation end-products (AGE), which have been reported as an emerging threat of early aging in the skin. Previous studies reported a reduction in survival of the HaCaT cell line exposed to 500 µM MGO. However, studies on primary keratinocytes are still limited. We evaluated the viability and proliferation of primary human epidermal keratinocytes (HEKa) under the exposure of MGO. We also employed H2DCFDA assay to quantify the generation of intracellular ROS due to MGO. Our study revealed a biphasic response in which lower doses of MGO (25 and 50 µM) increased viability, while the cellular toxicity began at higher concentrations of 100, 200, and 300 µM. The proliferation assay also suggests an overall reduction of primary epidermal keratinocytes exposed to 100 and 200 µM MGO after 24 and 48 hours of culture. Increasing ROS concentrations were also observed in cells treated with 100 and 200 µM MGO. Our data suggested that a lower concentration of MGO was required to induce cellular toxicity in primary human epidermal keratinocytes compared to the HaCaT cell line reported by another study, indicating different sensitivity to MGO.